PENGEMBANGAN “D’PASKEL” (DIYUN’S PASTEL KERING ABON LELE) SEBAGAI MAKANAN SELINGAN BALITA STUNTING 12–59 BULAN - Anggraeni Permatasari, Dian Ratna; Fitria, Mona; Priawantiputri, Witri; Hapsari, Agustina Indri (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2024)
Culinary products from local food ingredients such as shredded catfish and titi corn are nutrient-dense foods as alternative snacks for stunted toddlers aged 12 - 59 months, namely in the form of dry pastels made from wheat flour, butter, egg yolk, Moringa leaves as a source of vegetable protein, carrots as a source vitamin A, shredded catfish a source of animal protein, titi corn a source of carbohydrates, and cheese. The aim of this research is to determine the effect of the catfish and corn titi floss formulation on the quality (organoleptic properties and nutritional value) of D'PasKeL products. The research method was experimental with balanced treatment of catfish floss and titi corn, namely 43%: 57% and 15%: 85%. The results of the research showed that there were significant differences between catfish floss and titi corn in taste, color, aroma and overall (p < 0.05), except for texture, there was no significant difference (p > 0.05). The organoleptic test results show that the most preferred D'PasKeL formulation is formula 1 with a balance of catfish floss and titi corn of 43%: 57%. The nutritional content in the best formulation can meet the needs of stunted toddlers, namely 11% energy, 15% protein, 15% fat, 10% carbohydrates, 4% fiber, 13% iron, 72% vitamin A, and 16% zinc. The production costs incurred are IDR 1,300.00 for 1 serving.